Hubungan Literasi Kesehatan Mental dengan Distres Psikologis pada Mahasiswa Non-Kesehatan - Fauzi, Aisha; Suminar, Dewi Retno (Universitas Airlangga, 2023)
Mental health issues that develop in college students, particularly STEM students, require additional attention. This is also accompanied by STEM students' level of mental health literacy. This study aims to determine whether there is a correlation between mental health literacy and psychological distress in STEM students at the Sepuluh Nopember Institute of Technology. The Mental Health Literacy scale used to measure mental health literacy. The Kessler Psychological Distress (K10) used to measure psychological distress. The results of the research data analysis obtained a correlation value of 0,838 (p > 0,05). Mental health literacy does not indicate an existing correlation with psychological distress, thus implying that there might be other variables involved.